151k views
14 votes
4x + 2 (3x + 7) - 7x​

User Calycolor
by
4.9k points

2 Answers

14 votes

Answer:

3x+14

Explanation:

4x+2(3x+7)-7x

4x-7x+2(3x+7)

-3x+2(3x+7)

-3x+(2*3x+2*7)

-3x+(6x+14)

-3x+6x+14

answer: 3x+14

User Steven Ryssaert
by
5.4k points
3 votes

Answer:

3x + 14

Explanation:

2 x 3x = 6x 2 x 7 = 14, 6x + 4x = 10x - 7x = 3x + 14

therefore its:

3x + 14

User Wulf
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.